An environmental assessment through load capacity factor: the dynamic effects of technological cooperation grants and energy depletion in Pakistan - Ullah, Sami; Lin, Boqiang (Frontiers in Sustainable Energy Policy, 2025)
The global phenomenon of environmental deterioration often signifies the increase in ecological footprint and emissions levels that adversely affect the earth's biocapacity. This results from the use of substantial fossil fuels energy sources, industrialization, and extensive economic activities in developing countries. In this context, the study examine the impact of energy depletion, technical cooperation grants, and industrialization, on the load capacity factor of Pakistan from 1970 to 2022. To accomplish this, this study employs the innovative dynamic autoregressive distributed lag (ARDL) simulation approach, providing fresh insights that contrast with earlier conclusions. The authors contribute to focusing the supply-side dynamics of ecological deterioration indicators, namely load capacity, from the viewpoint of Pakistan, distinguishing our research from existing academic publications. Our results, however, demonstrate a markedly favorable effect of technical cooperation grants on the load capacity factor in enhancing environmental safety. Furthermore, energy depletion and industrialization adversely impact the load capacity dynamics, exacerbating environmental deterioration. Moreover, the study conducts a sensitivity analysis by comparing the results obtained using the load capacity factor with those derived from ecological footprints. Consequently, we advocate for the development of realistic policies to mitigate the adverse impacts of energy depletion and industrialization via the effective use of energy sources to preserve biodiversity.